Conservation building defects analysis on historical buildings / Nur Atiqah Razali - Razali, Nur Atiqah (Faculty of Architecture, Planning and Surveying, 2013)
The issue of this research is to find the usually defects occurred to the historical building in Malaysia. The purpose of this research is to identify and analyze the cause of defects happened. Besides that, within the completely research, we can identify the locations of the defects happened to the historical buildings in Malaysia. Besides that, we can analyzed of main defects happened to the historical buildings. This research mostly focused on the conservation defect analysis on historical buildings in Malaysia. As we know, building in Malaysia most exposed to the defects because of the climatic action. Some of these historic buildings in Malaysia are structurally sound and have undergone physical transformations to adapt to climatic conditions as well as the local way of life. Building defects usually occur in most historical buildings in Malaysia. Issues and problems related to building defects should be given serious attention and addressed promptly as they may damage the original architectural designs and materials that are applicable to the historical buildings in the long run. The focused case study of this research is the conservation buildings. Conservation buildings also can expose to the defects happened. It found that there are some conservation work approaches adopted in the project site which do not meet the conservation principles, philosophy and ethics as required by the international standard. So that, it also can give building damage or defects to the historical buildings in Malaysia. The techniques, methods and material that been use to build and construct the buildings is a main concern in conservation projects. There have several techniques or methods of building conservation that are restoration, preservation and reconstruction. Other than that, those techniques also need right considerations before conservation works was starting. It is important to avoid any damage and accident to the people and building in the current and future.